PENGEMBANGAN E-MODUL PENGOLAHAN LIMBAH ORGANIK SECARA ECO-ENZYME PADA MATERI GREEN CHEMISTRY UNTUK SISWA SMA KELAS X - Siagian, Nova Lestari; Yusbarina, Yusbarina; Utami, Lisa; Fatisa, Yuni (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
AbstractGreen Chemistry is a new lesson in Merdeka Curriculum, so students and teachers need additional teaching materials used to support the learning process. This research aimed at designing and testing e-module for processing organic waste by making eco-enzymes on Green Chemistry lesson, and it was tested its validity based on validation by material and media experts, teacher practicality test, and student response test. Design and Development Research (DDR) model was used in this research. This research was administered at the tenth grade of class 1 at State Senior High School 5 Pekanbaru. The validation result by material expertsshowed that the score was 98.63% with very valid category, the validation result by media experts showed that the score was 95.51% with very valid category, the teacher practicality test result showed that the score was 95.83% with very valid category, and the student response practicality test result showed that the score was 83.11% with very valid category. Based on the validation and practicalityresults obtained, it could be concluded that e-module for processing organic waste by making eco-enzymes on Green Chemistry lesson was appropriate to be test as an additional teaching material in Chemistry learning.Keywords: E-Module, Processing Organic Waste, Eco-Enzyme, Green Chemistry